(3TQM GdSjQ GdcHjQs - (3CHh HcQ eMeO Hf GHi Sgd GdSQNSis; (3eMeO GdTjHGfj , eMeO Hf GdMSf GdTjHGfj, GdTjHGfjs
(3ChdgG (B:s
(3jHOC HHGH GdLgGO heG jSY efg heG dGjSY efg s
(3BNQgG (B:s
(3EPG KHJ Mb GdeTJQi jQLY HGdKef ai ZfGFe GdeSdejf Ef cGfJ de JbSe hEf bSeJ ZQe Pdc ddeTJQi ef HjJ GdeGd hdjS Ydi GdPi jHGTQ GdHjY YgOI ai TF ef Pdc hdgPG UM VeGfg ddKef hGddg CYde hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3bhHdJ Ydi GdCUd Gdefbhdg efgs
(3HChdg agQSJHgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs